Eksistensi dan Peran Ekonomis Harta Wakaf - Susanto, Heru (State Institute of Islamic Studies (IAIN) Palu, 2016)
Waqf as social instrument of Islamic economy that its function based on good deeds, goodness, and brotherhood, has important role to empower and to increase the economic prosperity of the muslim society. In the hystory, waqf has been playing its important role to develop social living, economic prosperity, and social culture.Â Itâ€™s prooved in the history of Islamic philantrophy that its track still remained and can be seen in many Islamic countries like Egypt, Saudi Arabia, Turki, Kuwait etc. Waqf in those countries are growing better because managed professionally. To achieve the purpose of waqf (to increase social economic prosperity), it needs the change of muslims comprehension about waqf from traditionally into modern management, so that the waqf becomes productive and social economic prosperity can be achieved